Slow magic: agricultural R&D a century after Mendel - Pardey, Philip G.; Beintema, Nienke M. (International Food Policy Research Institute, 2001)
Standing on the brink of a biotechnology revolution in agriculture, it is timely to take stock of the investments and institutional trends regarding agricultural R&D worldwide. In this report we assemble and assess new and updated evidence regarding investments in agricultural R&D by public and private agencies, contrasting developments in rich and poor countries.The payoffs to investments in agricultural research are considerable, and appear to remain so, but there are new policy concerns about the roles of the public and private sectors in funding and carrying out the research, especially in light of the revolutionary changes in the underlying sciences and the incentives facing research (as intellectual property regimes become stronger and international trade in science and technologies grows). This report tracks trends in agricultural R&D over the past several decades.We also put research policies in a much longer timeframe, highlighting the critical importance that the accumulated stock of scientific knowledge has on today’s productivity performance and its effect on innovation and economic growth in the future.